Primary catastrophic antiphospholipid syndrome in an 8 year-old-girl - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Antiphospholipid syndrome (APS) is a disease characterized by recurrent arterial and venous thromboses. Rapidly progressive multiple thromboses leading to multiorgan failure occur in less than 1% of patients and named as catastrophic antiphospholipid syndrome (CAPS). We, hereby, describe an 8 year-old-girl with erythematous skin lesions progressing into purpura fulminans. The patient developed CAPS with the findings including proteinuria, microangiopathic hemolytic anemia, thrombocytopenia, arterial and venous thromboses demonstrated on skin biopsies. She was admitted to intensive care unit and received empirical antibiotics, anticoagulants, antiaggregants, steroids and intravenous immunoglobulins. The diagnosis of APS was confirmed by positive lupus anticoagulants, elevated anti beta-2 glycoprotein IgG and antiphospholipid IgG titers. Moreover, other than MTHFR-A1298C, MTHFR-C677T, factor V H1299R, beta fibrinogen-455 G >A heterozygosity indicating low risk for thrombophilia, no infectious, rheumatological or malignant etiologies were identified. Family history revealed Raynaud's phenomenon in a sister, interstitial lung disease, proteinuria and hematuria in paternal grandmother in addition to lupus anticoagulant positivity in father and 2 elder sisters. Her treatment included debridement of necrotic skin tissue, grefting and local mesenchymal stem cell application to upper thigh and lower leg region following oral azathioprine administration.
Keywords: Catastrofic antiphospholipid syndrome; Child; Purpura fulminans